The Risk of Congenital Anomalies by Fertility Treatment Modality. Issue 1 (January 2021) - Chung, Esther H.; Harris, Benjamin S.; Muasher, Suheil J.; Kuller, Jeffrey A.
Abstract : Importance: Up to 4% of all births in developed nations involve assisted reproductive technology (ART), along with other fertility treatment modalities. Thus, ART pregnancies constitute an important epidemiologic population with a known increased risk of congenital anomalies. In this review, we summarize current fertility treatment modalities and their associated risk of congenital anomalies. Objective: To review the risk of birth defects among pregnancies conceived with ART and other fertility treatments. Evidence Acquisition: Articles were obtained from PubMed and the American College of Obstetricians and Gynecologists and American Society of Reproductive Medicine committee opinions. Results: In vitro fertilization has been associated with a 25% to 50% increased risk of birth defects, including abnormalities of these organ systems: cardiovascular (25%–40% of anomalies), genitourinary (10%–60%), gastrointestinal (10%–20%), and musculoskeletal (10%–35%). Although the data are mixed, intracytoplasmic sperm injection has also been found to be associated with an increased risk of defects, particularly hypospadias, when compared with conventional in vitro fertilization. The risk among fresh versus frozen cycles and cleavage stage versus blastocyst transfers remains uncertain. There appears to be no significant added risk with preimplantation genetic testing, although more studies are needed. Ovulation induction with oral agents appears safe and not associated with an increased risk of anomalies. Oocyte cryopreservation also appears safe, but the data are still limited, requiring future investigation. Conclusions and Relevance: While the relative risk of birth defects among ART pregnancies is increased when compared with spontaneous conceptions, the absolute risk remains low. There are no standard screening recommendations for ART pregnancies. Per the American College of Obstetricians and Gynecologists, patients who have undergone ART should be counseled regarding the risk of birth defects and available antenatal evaluation, including fetal echocardiogram and detailed ultrasound evaluation. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: Following completion of this CME article, readers should be better able to assess risk factors for birth defects among individuals undergoing fertility treatment; explain available antenatal screening modalities for detection of common birth defects associated with ART; and identify available resources and recommendations on risk factors for birth defects associated with infertility treatment.